Manhaj Penafsiran Hamka: Telaah Ayat-Ayat Ahkam dalam Konteks Keindonesiaan - Ahmad Nabil Amir (Peradaban Journal of Religion and Society, 2023)
The paper discusses the underlying method and context of interpretation of legal verses as set forth by Hamka in his magnum opus, Tafsir al-Azhar. It looks into the historical background and dynamics of his interpretation of legal verses that bring forth significance breakthrough in the articulation of classical theoretical perspective of fiqh, maqasid (higher objective of Islamic law), maslahah (public good) and fundamental of syariah. The study is based on library research using qualitative and scientific approach. Relevant data were collected from primary and secondary sources and analyzed through descriptive, analytical and comparative technique. The finding shows that the Tafsir has bring forth significance breakthrough in legal interpretation that shed light on philosophical and contextual meaning of the ayah, projecting rational dan liberal understanding of the text, independent from classical interpretation and doctrine of traditional ruling and school of thought. It shed lights on universal dan dynamic religious spirit and reassertion and reconstruction of ijtihad and socio-legal reform, arguing for the significant local dynamics, norms and ethics of fiqh nusantara (Malay-Indonesian archipelago) which addresses contemporary needs of modern Indonesia’s complex multicultural and cosmopolite society.    Kajian ini membahas metode penelitian hukum yang dilakukan oleh Hamka dalam Tafsir al-Qur'an karangannya, Tafsir al-Azhar. Kajian ini bertujuan untuk melihat alur dan konteks pemikiran Hamka dalam kajian hukum dan syariah terkait dengan aspek pembaharuan ideologi hukum, fikih, maqasid, pemahaman maslahah dan ushul syariah. Metodologi penelitian adalah kualitatif dari jenis penelitian kepustakaan. Bahan penelitian diperoleh dari sumber primer dan sekunder yang terkait dan dianalisis secara deskriptif, analitis dan komparatif. Hasil kajian menyimpulkan bahwa Hamka mempunyai kesederhanaan dan keluasan pandangan hukum yang tidak terikat oleh doktrin dan ideologi mazhab. Ini menunjukkan pandangan klasik dan universal yang mempertahankan nilai kebebasan dan ijtihad serta semangat hukum yang rasional dan kontekstual yang dipengaruhi oleh fikih nusantara dengan tujuan mendekatkan pemahaman hukum dengan nuansa kehidupan masyarakat dan konteks perkembangan Islam di Indonesia yang modern dan kosmopolit.